Multi-Source Pathways of T Follicular Helper Cell Differentiation - Ma, Xiaoxue; Nakayamada, Shingo; Wang, Jun (Frontiers in Immunology, 2021)
T follicular helper (Tfh) cells participate in humoral immune by promoting inflammation and aiding B cells survival, proliferation, maturation, and generation autoantibodies. The plasticity of Tfh cells enables the immune system to adjust the direction of differentiation according to the degree of the immune response, regulate the germinal center (GC) response and maintain homeostasis. Tfh differentiation involves several signaling factors, including multiple cytokines, receptors, transcription factors and genes. The signal transducer and activator of transcription (STAT) family signaling pathways are crucial for Tfh formation. However, because of the multi-factorial and multi-stage features of Tfh differentiation, every STAT member plays a role in Tfh differentiation, but is not completely depended on. With the gradual recognition of different Tfh subsets (Tfh1, Tfh2, Tfh17), the process of Tfh differentiation can no longer be explained by straight-line derivation models. In this review, we summarize the roles of different STATs in mediating Tfh subsets, analyze the contributions of mutual restraint and cooperation among cytokine-STAT signals to terminal Tfh differentiation, and clarify the multi-source pathways of Tfh differentiation with a three-dimensional illustration.